Behavioural Response to a Sudden Health Risk : Dengue and Educational Outcomes in Colombia (2016)
This paper makes use of a short, sharp, unexpected health shock to examine the indirect behavioural response of the general public to a sudden shift in the perceived risk of a substantial deterioration of health and mortality. While existing work has been done estimating the direct effects of an epidemic on the afflicted families, we instead focus on assessing the indirect effect of a sudden epidemic on the population as a whole, mediated by the behavioural response to the sudden shift in the perceived risks of engaging in certain activities. Our analysis finds that the influence of the epidemic extends far beyond those directly afflicted: it essentially comprises a behavioural response to the fear of contracting the disease. Strikingly, we find that close to 4 fewer students, out of a typical class of 47 pupils, sit their school leaving examination for every additional 10 cases of severe Dengue per 10.000